Low-voltage bulk-driven self-biased ascode current mirror with bandwidth enhancement - Raj, N.; Singh, Ashutosh Kumar; Gupta, A. (Stuart Govan, 2014)
A low-voltage, high-performance, self-biased, cascode bulk-driven current mirror is proposed. Using the bulk-driven technique together with quasi-floating gate metal-oxide semiconductor transistors improves the overall circuit performance. A small-signal analysis validates the advantage of such an approach over conventional bulk-driven circuits. The proposed circuit has four times smaller input resistance and extended bandwidth by about three times over the same configuration using the conventional bulk mechanism. The circuit is simulated on UMC 0.18 μm technology node with the help of HSpice.